2019
DOI: 10.1038/s41598-019-51052-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Crystallographically Unresolved Cytoplasmic Loop in Stabilizing the Bacterial Membrane Insertase YidC2

Abstract: YidC, a bacterial member of the YidC/Alb3/Oxa1 insertase family, mediates membrane protein assembly and insertion. Cytoplasmic loops are known to have functional significance in membrane proteins such as YidC. Employing microsecond-level molecular dynamics (MD) simulations, we show that the crystallographically unresolved C2 loop plays a crucial role in the structural dynamics of Bacillus halodurans YidC2. We have modeled the C2 loop and used all- atom MD simulations to investigate the structural dynamics of Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…In E. coli, incoming substrates have been hypothesized to interact initially with the YidC C1 loop followed by interaction with a conserved arginine residue within transmembrane domain TM2 for insertion ( Kol et al, 2008 ; Kumazaki et al, 2014a , c ). More recently, molecular dynamics simulation showed that the crystallographically unresolved cytoplasmic C2 loop of BhYidC2 plays an important role in stabilizing this insertase’s structure ( Harkey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, incoming substrates have been hypothesized to interact initially with the YidC C1 loop followed by interaction with a conserved arginine residue within transmembrane domain TM2 for insertion ( Kol et al, 2008 ; Kumazaki et al, 2014a , c ). More recently, molecular dynamics simulation showed that the crystallographically unresolved cytoplasmic C2 loop of BhYidC2 plays an important role in stabilizing this insertase’s structure ( Harkey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…17,18,22,27 PepT St is the only POT symporter that has been crystallized in OCC, IF, and IF occ conformational states. 17,18,22,27 Hence, in this study we simulated all three available conformational states of PepT St via unbiased all-atom MD [30][31][32][33] with either E300 protonated or deprotonated. Additionally, we simulated the IF occ (LA) in all possible protonation combinations of E299, E300, and E400 residues, which resulted in a total of eight substrate bound systems (see methods for more details).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike its C1 loop, the BhYidC2 C2 loop was not structurally resolved by X-ray crystallography (Kumazaki et al, 2014c). Molecular dynamic (MD) simulations, however, predicted a contribution of the C2 loop in stabilizing protein structure, especially in reducing flexibility of the C1 loop by formation of an inter-domain salt bridge between D205 (C2) and K109 (C1) (Harkey et al, 2019). Structural analysis of BhYidC2 also revealed that its C1 loop is assessable to the cytoplasm, while the smaller C2 loop appears to be embedded within the lipid bilayer and probably involved in an interaction with lipid heads.…”
Section: Cytoplasmic Domains Impart Distinct Functional Attributes To Smyidc1 and Smyidc2mentioning
confidence: 99%
“…In light of in silico structure predictions, combined with insight gained from phenotypic assays, we hypothesized that specific interactions between cytoplasmic domains were responsible for particular structure-function attributes. In fact, Moradi and coworkers had proposed that formation of a salt-bridge between the C1 and C2 loops of B. halodurans YidC2 appears to stabilize the flexible C1 loop (Harkey et al, 2019). When the SmYidC1 and SmYidC2 cytoplasmic domains were evaluated, both paralogs contained multiple oppositely charged residues within close enough proximity (<3 Å) to form salt-bridges (Supplementary Table 6).…”
Section: Yidc1 and Yidc2 Cytoplasmic Domains Possess Distinct Intra-and Inter-domain Interactionsmentioning
confidence: 99%
See 1 more Smart Citation